Acute pancreatitis in children in University Malaya Medical Centre: A descriptive study / Farah Syuhada Mohd Radzi - Farah Syuhada, Mohd Radzi (2017)
Acute pancreatitis in children is uncommon but when it occurs, it can be associated with severe morbidity and mortality. The purpose of this study was to describe the clinical presentation, etiology, diagnosis, severity, management, outcome and follow up of acute pancreatitis in children in UMMC. Methods: Children and adolescent less than 18 years old, diagnosed with acute pancreatitis were recruited by searching DSM-ICD 10 code for acute pancreatitis in UMMC beginning from 1 st January 2007 till 31 st July 2017. Most patients recruited were gastroenterology and oncology patients. Patients were included if they are less than 18 years old and diagnosed with acute pancreatitis for the first time. Data described include clinical presentation, etiology, severity, diagnosis, management, outcome and follow up of acute pancreatitis. Results: There were 36 cases diagnosed with acute pancreatitis included. On average there were 3 cases per year diagnosed with acute pancreatitis in children in UMMC. Age rang from 2 to 18 years old (median age 10.5 years old). The most common cause of acute pancreatitis in UMMC is idiopathic (n=l6). Other causes include drug-induced (n=4), congenital biliary anomalies (n= 5), gallstones (n=3), post-ERCP (n=l), pancreaticobiliary anomaly (n=l) and hereditary (n= 2). The most common presenting symptoms were abdominal pain (n= 33) which were mainly epigastric pain followed by vomiting (n=I 8). Thirty six children diagnosed with acute pancreatitis in UMMC met at least 2 out 4 diagnostic criteria for acute pancreatitis thirty three children had typical abdominal pain, 23 had high urine amylase, 23 had high serum amylase, 18 had both high serum and urine amylase and 23 patients had abnormal radiological imaging. Pancreatic enlargement is the most common radiological finding suggestive of acute pancreatitis in children in UMMC (n=13). Other abnormal radiological findings were dilated pancreatic duct (n=4), pancreatic pseudocyst (n=3), peripancreatic fluid (n=l) and pancreatic mass (n=l). There were a total of 33 children had mild disease and 3 with severe acute pancreatitis. Twenty-nine children with acute pancreatitis were given supportive treatment in which 27 of them had mild disease and 2 had severe disease. Seven children with mild disease were 4 patients with choledochal cyst and 3 with gallstones. All seven patients undergo surgery. Only one patient with severe disease underwent pseudocyst drainage because of worsening abdominal distension and peritonitis. Most common acute complication in children in UMMC were pancreatic pseudocsyt (n=3). From 36 children with acute pancreatitis, 18 resolved spontaneously, 8 had acute recurrent pancreatitis and 9 had chronic pancreatitis. Two children with chronic pancreatitis developed Jong term complications. One patient had Diabetes Mellitus requiring insulin and the other had malabsorption on CREON. There were 3 deaths but it was not related to acute pancreatitis, 2 due to relapse ALL and 1 due to hypovolaemic shock post choledochal cyst resection. Out of 33 children who are still alive, 20 children still continue their follow up and 13 were lost to follow up. Conclusion: Paediatric pancreatitis is rare in children in UMMC. Most acute pancreatitis in children is mild and resolve spontaneously with medical and supportive treatment. Approximately about 5% of patients with acute recurrent and chronic pancreatitis may develop complications. Proper monitoring and follow up is important in patient with acute pancreatitis.